Effect of exercise-based counselling intervention for female school administrators with experience of work-family conflict: an exploratory study - Patricia Uzoamaka Agu; Daphney Mawila-Chauke; Moses Onyemaechi Ede; Saint Oliver R. Ngwoke (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background According to the evidence, female administrators are forced to fill both domestic and administrative tasks in their families and places of employment. They occasionally face demands from these roles that are out of their control. As a result, they experience fatigue and conflict from these demands. Based on these reasons, we studied the effects of an exercise-based counselling intervention on work-family conflict and occupational dysfunctional thinking in a sample of female educational administrators in light of these circumstances. Methods A randomized control design was used, and a total of 86 school principals took part in the survey. Using scales to measure work-family conflict, participants were tested before and then tested twice (post-test and follow-up test) after completing an exercise-based counseling intervention. The intervention lasted for 14 weeks, with each session lasting one hour. Meanwhile, those in the comparison group were placed on a waitlist. The intervention aimed to enhance participants’ perceptions of work-family life. Univariate analysis, partial eta square analysis, and repeated measures analysis of variance were used to analyze the data that had been obtained. Results The results showed that, among female administrators who had received the exercise-based counselling intervention, there had been a considerable improvement in a decrease in work-family conflict management. The results also suggest a statistically significant effect of time on work-family conflict among female administrators. The follow-up result reveals that the effectiveness of exercise-based counselling intervention was maintained over time in reducing work-family conflict. Conclusion The conclusion suggests that female administrators of schools exposed to exercise-based counselling intervention understand, perceive, and interpret conflicting work-family issues realistically, and that reduced work-family conflict. Trial registration The study was registered retrospectively on 29/09/2024 123,702 with UMIN Clinical Registry UMIN000055666.